Rachunek kosztów działań w przedsiębiorstwie handlowym - studium przypadku - Januszewski, Arkadiusz (Activity based costing in a trade company - case study, 2006)
This paper presents a model of activity-based Costing developed for a medium-sized wholesale and retail enterprise. The model has been applied in the environment of a stand-alone ABC modeling software. The implementation project aimed at developing a system of measuring profitability for numerous clients and suppliers of the company. In order to do this, above 30 kinds of resources categorized in 6 groups, 5 sorts of processes, 22 types of activities, as well as near 400 clients and over 100 suppliers have been identified within the model. Over 9500 relations between the elements of the model have been defined. The paper describes subsequent steps of implementing the model into IT environment, i.e. defining resources, activities and cost objects, cost flows mapping, data inputting, calculating relevant outcome figures and analysis of final results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 56-67